Close Contact Tracing and Risky Area Identification Using Alpha Shape Algorithm and Binary Contact Detection Model Based on Bluetooth 5.1 - Qianfeng Lin; Jooyoung Son (Journal of Eta Maritime Science)
This study presents a novel approach to managing disease outbreaks on cruise ships by integrating Bluetooth 5.1 technology, a Binary Contact Detection Model, and an alpha shape algorithm. By harnessing the precise data capture capabilities of Bluetooth 5.1, this study accurately tracks interpersonal interactions and delineated high-risk areas, effectively enhancing close contact tracing and disease surveillance efforts. The Binary Contact Detection Model utilizes In-phase (I) and Quadrature (Q) data to identify close contacts with high accuracy, while the alpha shape algorithm helps in mapping out areas most susceptible to disease transmission. The combined use of these technologies represents a significant advancement in public health surveillance, offering a method to enhance safety and mitigate the spread of infections on cruise ships.